Serum Levels of TNF-α, IL-12/23 p40, and IL-17 in Psoriatic Patients with and without Nail Psoriasis: A Cross-Sectional Study - Aikaterini Kyriakou; Aikaterini Patsatsi; Timoleon-Achilleas Vyzantiadis; Dimitrios Sotiriadis (The Scientific World Journal)
Nail involvement has started playing a major role in the overall assessment and management of psoriatic disease. Biologics indicated for moderate to severe chronic plaque psoriasis are shown to be beneficial in nail disease. This study aimed to assess and compare the serum levels of TNF-α, IL-12/23 p40, and IL-17 in psoriatic patients with and without nail involvement. 52 consecutively selected patients with chronic plaque psoriasis were included in this cross-sectional study. Patients were studied and analyzed after they had been divided into 2 groups regarding the presence (n = 24) or not (n = 28) of nail psoriasis. The mean serum levels of TNF-α were significantly higher in the group of psoriatic patients with nail lesions compared to those without (t-test; 5.40 ± 1.17 versus 3.80 ± 1.63, P = 0.026). However, the median serum levels of both IL-12/23 p40 (Mann-Whitney; 92.52 (34.35–126.87) versus 150.68 (35.18–185.86), P = 0.297) and IL-17 (Mann-Whitney; 28.49 (0.00–28.49) versus 8.59 (0.00–8.59), P = 0.714) did not significantly differ between the 2 groups. These results confirm the important role of TNF-α in the pathogenesis of nail psoriasis and may suggest that anti-TNF agents could be more beneficial in psoriatic nail disease than agents targeting IL-12/23 p40 or IL-17 and its receptors.